Communicating aims of the political TV-advertisement and means of their realization (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
In the article the political TV-advertisement as the particular type of texts is characterized, it’s communicating aims are determined. The author proves the connection of political TV-advertisement’s composition, language peculiarities and the purpose of these texts to influence the mass consciousness.
Keywords: informing and communicating processes; political advertisement; image; manipulation by consciousness